2015
DOI: 10.5032/jae.2015.03052
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Classroom Strategies that Prepare College Graduates for Workplace Success

Abstract: In our increasingly competitive and rapidly changing world, it is critical that college graduates enter the workforce with the requisite skills for lasting success. However, recent studies suggest employers increasingly identify a workforce readiness gap in core applied skills, which must be bridged by company investment. Teaching strategies that develop applied skills will better prepare graduates for the workforce. The purpose of this study was to describe the classroom strategies of faculty instructors at V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…A study by Talent Corporation Malaysia (TalentCorp) and the Institute of Labour Market Information and Analysis (ILMIA) found that the top three difficulties companies face in filling up critical occupations are (1) expected standards that are not met by the applicants; (2) applicants do not have critical employability skills such as communication and interpersonal skills; and (3) applicants have the necessary academic qualifications, but have unrealistic expectations for salary and rewards (TalentCorp Malaysia, 2016). This problem is further International Journal of Human Resource Studies ISSN 2162-3058 2018 intensified by the lack of collaboration between the HEIs and the industries (Govindaraju and Wong, 2011;Rateau, Kaufman and Cletzer, 2015). Hanapi and Nordin, 2014;Rahmat, Ayub and Buntat, (2016) argue that Malaysia faces an acute graduate unemployment problem not because of limited employment opportunities, but mainly because of graduates who are not work-ready.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Talent Corporation Malaysia (TalentCorp) and the Institute of Labour Market Information and Analysis (ILMIA) found that the top three difficulties companies face in filling up critical occupations are (1) expected standards that are not met by the applicants; (2) applicants do not have critical employability skills such as communication and interpersonal skills; and (3) applicants have the necessary academic qualifications, but have unrealistic expectations for salary and rewards (TalentCorp Malaysia, 2016). This problem is further International Journal of Human Resource Studies ISSN 2162-3058 2018 intensified by the lack of collaboration between the HEIs and the industries (Govindaraju and Wong, 2011;Rateau, Kaufman and Cletzer, 2015). Hanapi and Nordin, 2014;Rahmat, Ayub and Buntat, (2016) argue that Malaysia faces an acute graduate unemployment problem not because of limited employment opportunities, but mainly because of graduates who are not work-ready.…”
Section: Introductionmentioning
confidence: 99%
“…The need for 21 st century skill development is supported empirically, suggesting those skills better prepare students for 21 st century careers (Casner-Lotto, Barrington, & Wright, 2006;Rateau, Kaufman, & Cletzer, 2015). It is possible that 21 st century skills can be developed in a number of different ways including through inquiry-based teaching, experiential learning activities, and involvement in FFA.…”
Section: Review Of Literaturementioning
confidence: 99%
“…If the United States is to continue feeding and clothing an ever-increasing population, it is essential that today's college students be properly prepared to fill the agricultural jobs of tomorrow (Goerker, Smith, Fernandez, Ali, & Goetz, 2015). Recent trends have revealed that employers seek graduates who leave their college or university prepared not only with career-or situation-specific technical skills, but also with higher-order behavioral skills that can be applied to many different needs, issues, and careers (Bentley University, 2014;Casner-Lotto, Barrington, & Wright, 2006;Landrum, Hettich, & Wilner, 2010;Paranto & Kelkar, 2000; Partnership for 21 st Century Learning, 2015; Rateau, Kaufman, & Cletzer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Through 2020, 58% of projected agricultural job openings are expected to be agricultural business, education, communication, management, or governmental positions that actively require higher-order behavioral, interpersonal, leadership, and decision-making skills (Goerker et al, 2015). In order to succeed in these future agricultural careers, students must not only possess vocation-specific capabilities, but also master such abilities as critical thinking, leadership, teamwork, communication, creativity, adaptability, and accountability (Bentley University, 2014;Casner-Lotto, Barrington, & Wright, 2006;Landrum, Hettich, & Wilner, 2010;Paranto & Kelkar, 2000; Partnership for 21 st Century Learning, 2015; Rateau, Kaufman, & Cletzer, 2015).…”
Section: Introductionmentioning
confidence: 99%